Anthropometric profiles of 8-11 year old children from a low-income setting in South Africa - Sandra S. Pretorius; Natalia Neophytou; Estelle D. Watson (BMC, 2019)
Abstract Background Communities in low-to-middle income countries undergoing rapid urbanisation as well as nutrition transition are particularly at risk for associated health issues such as overweight and obesity. South Africa has a double-burden of both under- and over-nutrition, creating some uncertainty as to where to direct healthcare interventions. Therefore, providing anthropometric data in vulnerable populations, such as in early childhood, is much needed. Methods This observational study assessed height, weight, head circumference and age-adjusted BMI in 1785 Grade 4 (9.5 ± 0.7 years old) learners from 12 schools in two different areas in South Africa. Results Overall, the results of this study found a higher prevalence of overnutrition (>95th percentile for age-adjusted BMI) than undernutrition (<15th percentile for age-adjusted BMI), 27.3% versus 12.4% respectively. Although the boys were significantly older and taller than the girls in this sample, there were no significant sex differences between boys and girls for BMI (19.9 kg/m2 ± 6.0 vs 20 kg/m2 ± 5.8, p = 0.59). Significant differences were found between peri-urban and urban areas for undernutrition (16.1% versus 9.5%, p < 0.001) and overnutrition (9.7% versus 41.2%, p < 0.001). Conclusion South African children living in urban areas are particularly vulnerable to high rates of overweight and obesity. Therefore, interventions that are area and context specific are needed to address the issues of malnutrition in South Africa.